Universality of Meyer-Neldel Compensation rule (MNCR): Case study of thermally assisted a.c. conduction after laser irradiation. (October 2018) - Kumar, Amit; Mehta, N.
Abstract: In the current article, the influence of four different cw-lasers on the thermally activated a c. conduction of a novel quaternary chalcogenide glassy semiconductor Se72 Te20 Sn2 Cd6 has been reported at different audio frequencies. We have used four different laser sources of wavelengths lying in UV–Vis-IR region. The variation of a c. conductivity with temperature obeys the Arrhenius relation for all the four laser light sources. Further analysis confirms that pre-exponential factor of thermally governed a c. conduction and the activated energy involved in the phenomenon follows MNCR. It is also found that this correlation remains independent of laser wavelength. Highlights: Observed unique universality of MNCR for thermally-activated a c. conduction. Laser irradiation is used as external perturbation. MNCR remains unaffected for laser irradiation of wavelengths in UV–Vis-IR range.